Thermal tolerance of herring (Clupea harengus) early embryogenesis in relation to temporal temperature dynamics in the Baltic Sea - Vivian Fischbach; Flemming T. Dahlke; Paul Kotterba; Guilherme Pinto; Dorothee Moll; Timo Moritz; Patrick Polte (Journal of Thermal Biology, 2026)

Stock Rebuilding in a Mixed‐Population Fishery Context: The Case of North Sea and Western Baltic Herring - Vanessa Trijoulet; Valerio Bartolino; Dorte Bekkevold; Benoit Berges; Henrik Mosegaard; Patrick Polte; Christoffer Moesgaard Albertsen (Fisheries Management and Ecology, 2026)
Managing and giving advice for mixed‐population fisheries of the same species can be challenging due to difficulties in predicting stock mixing, technical interactions, and in ensuring precautionary stock dynamics. Most fish species consist of several populations all of which need to be sustainably managed to preserve biodiversity and resilience to environmental changes, and to sustain productive fisheries. Mixing of populations of the same species with different productivity represents additional challenges for assessment and management. In such cases, there is a need to develop assessment and advice methods to consider mixed stocks and advise managers on fishing opportunities. In this study, we develop a framework including multifleet multi‐stock assessment models and forecasts where future stock dynamics depend on stock mixing, fleet‐specific fishing opportunities, and management in place. This framework is applied to the large North Sea herring stock and the overexploited western Baltic herring stock, which in part of their distribution areas are found to be mixed in both catches and surveys. The framework is used to investigate the trade‐offs between stock rebuilding and fishing opportunities in a mixed fishery. The study shows that spatial management implying transfer of quotas away from the areas where the stocks mix and towards the stock in good condition could help stock rebuilding without reducing overall fishing opportunities, however with a slower rebuilding rate compared to a more drastic fishery closure. The implementation of quota transfer should however consider the spatial relocation of fishing opportunities to avoid catch advice overshoot and inflated quotas.

Worldwide Appraisal of Knowledge Gaps in the Space Usage of Small Pelagic Fish: Highlights Across Stock Uncertainties and Research Priorities - Ignacio A. Catalán; Noelle M. Bowlin; Matthew R. Baker; Florian Berg; Aaron Brazier; Timothée Brochier; Jana M. Del Favero; Susana Garrido; Douglas F. M. Gherardi; Stefanie Haase; Martin Huret; Matthias H. F. Kloppmann; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Maternal, temperature, and seasonal effects on yolk-sac larvae of Atlantic herring Clupea harengus in the western Baltic Sea - Amy T. Huang; Katharina Alter; Patrick Polte; Myron A. Peck (Journal of Experimental Marine Biology and Ecology, 2025)

Future climate change and marine heatwaves - Projected impact on key habitats for herring reproduction - Matthias Gröger; Florian Börgel; Sven Karsten; H.E. Markus Meier; Kseniia Safonova; Cyril Dutheil; Aurore Receveur; Patrick Polte (Science of The Total Environment, 2024)

A wolf in sheep's clothing: Planktivorous A tlantic herring preys on demersal fishes in coastal waters - Paul Kotterba; Dorothee Moll; Helmut Winkler; Annegret Finke; Patrick Polte (Ecology, 2024)

Population genetics of the hound needlefish Tylosurus crocodilus (Belonidae) indicate high connectivity in Tanzanian coastal waters - Said S. Mgeleka; Mathew Ogalo Silas; Cretus Mtonga; Cyrus Rumisha; Elina Viinamäki; Patrick Polte; Mattias Sköld; Monika Winder; Martin Gullström (Marine Biology Research, 2023)

Correction: Caught in the middle: bottom up and top down processes impacting recruitment in a small pelagic fish - Marta Moyano; Björn Illing; Anna Akimova; Katharina Alter; Valerio Bartolino; Gregor Börner; Catriona Clemmesen; Annegret Finke; Tomas Gröhsler; Paul Kotterba; Lina Livdane; Felix Mittermayer; et al. (Reviews in Fish Biology and Fisheries, 2023)

Caught in the middle: bottom-up and top-down processes impacting recruitment in a small pelagic fish - Marta Moyano; Björn Illing; Anna Akimova; Katharina Alter; Valerio Bartolino; Gregor Börner; Catriona Clemmesen; Annegret Finke; Tomas Gröhsler; Paul Kotterba; Lina Livdane; Felix Mittermayer; et al. (Reviews in Fish Biology and Fisheries, 2022)
Understanding the drivers behind fluctuations in fish populations remains a key objective in fishery science. Our predictive capacity to explain these fluctuations is still relatively low, due to the amalgam of interacting bottom-up and top-down factors, which vary across time and space among and within populations. Gaining a mechanistic understanding of these recruitment drivers requires a holistic approach, combining field, experimental and modelling efforts. Here, we use the Western Baltic Spring-Spawning (WBSS) herring ( Clupea harengus ) to exemplify the power of this holistic approach and the high complexity of the recruitment drivers (and their interactions). Since the early 2000s, low recruitment levels have promoted intense research on this stock. Our literature synthesis suggests that the major drivers are habitat compression of the spawning beds (due to eutrophication and coastal modification mainly) and warming, which indirectly leads to changes in spawning phenology, prey abundance and predation pressure. Other factors include increased intensity of extreme climate events and new predators in the system. Four main knowledge gaps were identified related to life-cycle migration and habitat use, population structure and demographics, life-stage specific impact of multi-stressors, and predator–prey interactions. Specific research topics within these areas are proposed, as well as the priority to support a sustainable management of the stock. Given that the Baltic Sea is severely impacted by warming, eutrophication and altered precipitation, WBSS herring could be a harbinger of potential effects of changing environmental drivers to the recruitment of small pelagic fishes in other coastal areas in the world. Graphical abstract

Disentangling seasonal from maternal effects on egg characteristics in western Baltic spring‐spawning herring Clupea harengus - Amy T. Huang; Katharina Alter; Patrick Polte; Myron A. Peck (Journal of Fish Biology, 2022)
In marine fishes, the timing of spawning determines the environment offspring will face and, therefore, the chances of early life stage survival. Different waves of Atlantic herring Clupea harengus spawn throughout spring in the western Baltic Sea, and the survival of offspring from early in the season has been low in the most recent decade. The authors assessed changes in egg traits from early, middle and late phases of the spawning season to examine whether seasonal and/or maternal effects influenced embryo survival. At each phase, fertilized eggs of six to eight females were incubated at two temperatures (7 and 13°C), and egg size, fertilization success, mortality and time to hatch were recorded. A compilation of data from 2017 to 2020 spawning seasons indicated that mean total length of females decreased with progression of the season and increasing in situ water temperature. For the sub‐set of females used in the laboratory study, early spawners were 7.6% larger and produced 14.2% larger eggs than late‐spring spawners. Fertilization success was consistently high (>90%), and mortality to hatch was low ( e.g. , seasonal match–mismatch dynamics with prey) as more likely causes of mortality.

Seasonal depth distribution and thermal experience of the non-indigenous round goby Neogobius melanostomus in the Baltic Sea: implications to key trophic relations - Jane W. Behrens; Marie P. Ryberg; Heli Einberg; Redik Eschbaum; Ann-Britt Florin; Wlodzimierz Grygiel; Jens Peter Herrmann; Bastian Huwer; Karin Hüssy; Elina Knospina; Kristiina Nõomaa; Daniel Oesterwind; et al. (Biological Invasions, 2022)
Native to the Ponto-Caspian region, the benthic round goby ( Neogobius melanostomus ) has invaded several European inland waterbodies as well as the North American Great Lakes and the Baltic Sea. The species is capable of reaching very high densities in the invaded ecosystems, with not only evidence for significant food-web effects on the native biota and habitats, but also negative implications to coastal fishers. Although generally considered a coastal species, it has been shown that round goby migrate to deeper areas of the Great Lakes and other inland lakes during the cold season. Such seasonal movements may create new spatio-temporal ecosystem consequences in invaded systems. To seek evidence for seasonal depth distribution in coastal marine habitats, we compiled all available catch data for round goby in the Baltic Sea since its invasion and until 2017. We furthermore related the depths at capture for each season with the ambient thermal environment. The round goby spend autumn and winter at significantly deeper and offshore areas compared to spring and summer months; few fish were captured at depths 25 m. The thermal conditions at which round goby were caught varied significantly between seasons, being on average 18.3 °C during summer, and dropping to a low 3.8 °C during winter months. Overall, the fish sought the depths within each season with the highest possible temperatures. The spatial distribution of the round goby substantially overlaps with that of its main and preferred prey (mussels) and with that of its competitor for food (flatfish), but only moderately with the coastal predatory fish (perch), indicating thereby very complex trophic interactions associated with this invasion. Further investigations should aim at quantifying the food web consequences and coupling effects between different habitats related to seasonal migrations of the round goby, both in terms of the species as a competitor, predator and prey.

Reduced Reproductive Success of Western Baltic Herring (Clupea harengus) as a Response to Warming Winters - Patrick Polte; Tomas Gröhsler; Paul Kotterba; Lena von Nordheim; Dorothee Moll; Juan Santos; Paco Rodriguez-Tress; Yury Zablotski; Christopher Zimmermann (Frontiers in Marine Science, 2021)
Shallow estuaries, bays, and lagoons are generally considered hot spots of ocean productivity that often adjust rapidly to seasonal variations in atmospheric temperatures. During spring when biological reproductive processes begin in the temperate zones, regional climate variability can be immense and uncovering a non-linear biological response, such as fish recruitment to changing temperature regimes might be challenging. Using herring as a paradigm for a response of coastal spring productivity to regional climate drivers, we demonstrated how the annual timing of spawning periods can significantly affect the reproductive success of spring-spawning herring ( Clupea harengus ) in the western Baltic Sea. An investigation of spawning phenology in consecutive years indicated a temperature threshold range of 3.5–4.5°C triggering initial spawning in the coastal zone. Based on this finding, we analyzed the timing of larval hatching peaks, larval survival and recruitment to the adult population relative to multi-decadal time-series of seasonal sea-surface temperatures. The results revealed that the late seasonal onset of cold periods the corresponding elongation of the period where larvae hatch from the eggs and early larval hatching peaks significantly reduced larval production in a coastal nursery area and finally lead to a reduced abundance of juveniles in the entire distribution area. Using a combination of field research and time series analysis, we presented precedence for shifting regional winter regimes providing a present-day stressor to reproductive capacity of a central component of the coastal food web.

Elemental Inventory in Fish Otoliths Reflects Natal Origin of Atlantic Herring (Clupea harengus) From Baltic Sea Juvenile Areas - Dorothee Moll; Paul Kotterba; Klaus Peter Jochum; Lena von Nordheim; Patrick Polte (Frontiers in Marine Science, 2019)

Impact of Spawning Substrate Complexity on Egg Survival of Atlantic Herring (Clupea harengus, L.) in the Baltic Sea - Lena von Nordheim; Paul Kotterba; Dorothee Moll; Patrick Polte (Estuaries and Coasts, 2018)

Storm-Induced Atlantic Herring (Clupea harengus) Egg Mortality in Baltic Sea Inshore Spawning Areas - Dorothee Moll; Paul Kotterba; Lena von Nordheim; Patrick Polte (Estuaries and Coasts, 2018)

Predation on Atlantic herring ( Clupea harengus ) eggs by the resident predator community in coastal transitional waters - Paul Kotterba; Dorothee Moll; Cornelius Hammer; Myron A. Peck; Daniel Oesterwind; Patrick Polte (Limnology and Oceanography, 2017)
Atlantic herring ( Clupea harengus ) migrates from offshore to coastal areas to spawn and their eggs and larvae may substantially increase prey resources for resident predators. We combined an in situ predator exclusion experiment using eggs naturally spawned on submerged aquatic vegetation and field observations of predator abundance to estimate the magnitude of predation mortality of herring eggs. During our predator exclusion experiment, performed in an important spawning ground in the southwest Baltic Sea, 20% of the herring eggs were consumed resulting in an extrapolated predation of 42% of all eggs between spawning and hatch. Abundance and stomach content analyses indicated that one predator (threespine stickleback, Gasterosteus aculeatus ) was responsible for the majority of the predation impact. Predation mortality estimates from this in situ study were more than 10‐fold higher than those of an empirical egg predation model for the same predator in the same region. Our findings highlight the potential of resident predators to regulate the survival of early life stages of ocean‐going fishes that rely on the nursery functions of inshore transitional waters.

Predation of threespine stickleback ( Gasterosteus aculeatus ) on the eggs of Atlantic herring ( Clupea harengus ) in a Baltic Sea lagoon - Paul Kotterba; Carsten Kühn; Cornelius Hammer; Patrick Polte (Limnology and Oceanography, 2014)
We analyzed the predation of threespine stickleback ( Gasterosteus aculeatus ) on the spawn of Atlantic herring ( Clupea harengus ) in a mesohaline lagoon of the Baltic Sea, hypothesizing a significant predation effect of a resident estuarine fish on the recruitment of an anadromous oceanic species. A predator exclusion field experiment using artificially spawned experimental units was combined with tank feeding experiments to estimate the effects of temperature and prey density on the herring egg consumption by estuarine G. aculeatus . The predator exclusion experiment showed a significant mortality of herring eggs caused by estuarine predatory fish species. A strong increase in the consumption of herring eggs by sticklebacks was observed between 11°C and 15°C (Q 10 = 3.15). Additionally, we found a significant positive correlation between egg concentration per area and predation intensity. Nearly all eggs were consumed at concentrations ≥ 25 eggs cm −2 , but predation was less intense at egg concentrations below that threshold. Field data on herring egg concentrations, stickleback abundances, and stomach contents were combined with the findings of the experiments to estimate the percentage of spawned herring eggs that is consumed by the local stickleback (M PS ). The highest M PS (11.4%) was estimated for a week in April in the second half of the spawning season. We conclude that stickleback predation on herring eggs potentially affects the local herring year class strength.

Biotic and abiotic controls on body size during critical life history stages of a pelagic fish, Pacific herring ( Clupea pallasii ) - Jonathan C. P. Reum; Timothy E. Essington; Correigh M. Greene; Casimir A. Rice; Patrick Polte; Kurt L. Fresh (Fisheries Oceanography, 2013)
Variation in growth and body size during critical life history stages can have important implications for life history schedules and survivorship. For P acific herring ( Clupea pallasii ), there is still debate as to whether juvenile body size is governed by density‐dependent or ‐independent processes and few have evaluated whether the relative importance of either process shifts over the course of early ontogeny. We used a unique data set consisting of seasonal measurements of abundance, body size, and spatial distribution within a semi‐enclosed basin of P uget S ound ( W ashington S tate, U . S . A .) to measure the relative importance of temperature and cohort abundance on body size at distinct time periods, and evaluated whether density‐dependent habitat shifts might be responsible for density‐dependent growth. Over the 9 years of sampling (2001–2010) midsummer body size was positively related to temperatures experienced during the egg/yolk sac and larval stages and unrelated to cohort abundance. However, fall body size was negatively correlated with abundance and uncorrelated with both midsummer body size and temperature, indicating a shift from density‐independent to density‐dependent control over the course of the growing season. Thus, density‐dependent effects may supplant density‐independent effects exhibited early in herring life history. Our data on spatial distributions of herring and their zooplankton prey indicate that density‐dependent reductions in growth may be explained by density‐dependent habitat shifts that lead to reduce overlap of herring with zooplankton. Evidence of density‐dependent growth in marine fish populations is often attributed to exploitative competition, but our results suggest that these patterns may partly be mediated by density‐dependent distribution expansions in to prey‐poor habitat.

The contribution of seagrass beds (Zostera noltii) to the function of tidal flats as a juvenile habitat for dominant, mobile epibenthos in the Wadden Sea - Patrick Polte; Anja Schanz; Harald Asmus (Marine Biology, 2005)